Distribution Records and Conservation Status of Turtles in Chitwan, Nepal - Pun, Shyam Kumar; Stanford, Craig B.; Khadka, Bed Bahadur (Journal of Institute of Science and Technology, 2023)
Turtle is one of the oldest reptile groups of which 18 species are reported in Nepal. Eight sites were surveyed for turtles in Chitwan. Data were collected by both direct and indirect methods. Nine turtle species and a total of 36 specimens were recorded in Chitwan. Indotestudo elongata and Nilssonia hurum were the most frequently recorded species. Morphometric measurements of seven turtles were also recorded. Madi (41.7%) was found to contain the highest species richness in the study area. This study also provides information on anthropogenic threats and potential remedies that will help to prevent the extinction of Nepal's turtles.